Positive mental health among cancer survivors: overlap in psychological well-being, personal meaning, and posttraumatic growth - Holtmaat, K. (Support Care Cancer, 2018)
PURPOSE: Positive mental health involves theoretical constructs like psychological well-being, personal meaning, and posttraumatic growth. This study aims to provide empirical insight into possible overlap between these constructs in cancer survivors. METHODS: Within the context of a randomized controlled trial, 170 cancer survivors completed the patient-reported outcome measures (PROMs) Ryff’s Scales of Psychological Well-Being (SPWB), Personal Meaning Profile (PMP), and Posttraumatic Growth Inventory (PTGI). Exploratory factor analysis (EFA) on the subscales of these PROMs, as well as structural equation modeling (SEM), was used to explore overlap in these three constructs. RESULTS: The EFA resulted in a three-factor solution with an insufficient model fit. SEM led to a model with a high estimated correlation (0.87) between SPWB and PMP and lower estimated correlations with PTGI (respectively 0.38 and 0.47). Furthermore, the estimated correlation between the subscales relation with God (PMP) and spiritual change (PTGI) was high (0.92). This model had adequate fit indices (χ(2)(93) = 144, p = .001, RMSEA = 0.059, CFI = 0.965, TLI = 0.955, SRMR = 0.061). CONCLUSIONS: The constructs psychological well-being and personal meaning overlap to a large extent in cancer survivors. Posttraumatic growth can be seen as a separate construct, as well as religiosity. These findings facilitate researchers to select the appropriate PROM(s) when testing the effect of a psychosocial intervention on positive mental health in cancer survivors. RELEVANCE: An increasing number of psychosocial intervention trials for cancer survivors use positive mental health outcomes. These constructs are often multifaceted and overlapping. Knowledge of this overlap is important in designing trials, in order to avoid the pitfalls of multiple testing and finding artificially strengthened associations. NETHERLANDS TRIAL REGISTER: NTR3571 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00520-018-4325-8) contains supplementary material, which is available to authorized users.